Efektifitas Implementasi Aktivitas Mengkomunikasikan Berbasis Kepala Bernomor Dalam Meningkatkan Dimensi Proses Kognitif - Trisnayanti, Wayan Ririn (Universitas Pendidikan Ganesha, 2017)
The purpose of this study is to determine the effectiveness of the implementation of a significant dimension of cognitive processes between students who were taught by the activity of communicating head-based communicating with students who were taught by conventional learning model in third grade students of SD in Buleleng Regency. This research was quasi experimental research with Non Equivalent Posstest Only Control Group Design design. The data were collected by using objective and esay tests. The data were analyzed by using descriptive statistics and inferential statistics. The results of this study showed that the activity of communicating head-based communicating effectively increase the dimension of student cognitive process. It can be seen from the average value of experimental group which was in very high category and the average value of the control group was in hig category. So experiment = 28,5> control = 21,05, and result of hypothesis test by using t-test was obtained tcount bigger than ttable (tcount = 3,62> ttable = 2,93)